Klasifikasi ABC dan Peramalan ARIMA Inventory Usaha Kecil Menengah Stokis Pakaian Muslim - Alamanda Chatartica; Kursehi Falgenti (Jurnal Inovtek Polbeng Seri Informatika, 2022)
The problem faced by many SMEs is the imbalance between demand and supply. As one of the SMEs, Stockist C-Geulis often faces the problem of unavailable product stock while orders are not yet available. This research aims to identify high-value and high-demand products and predict minimum and maximum inventory levels for the following month. The method for determining high-value products is ABC analysis, while the minimum and maximum inventory predictions use the ARIMA (Autoregressive Integrated Moving Average). The data for stock forecasting uses sales data from January 2019 to June 2021. The results show that ABC analysis based on sales value includes four class A products, three class B products, and eight class C products. The forecast results show that the inventory forecast data for three periods does not meet the assumption of stationarity to the average because a level 1 differentiation process is carried out so that the data becomes stationary. The ARIMA models produced are ARIMA (1,1,1) for Batik C-Geulis products and Busui C-Geulis and ARIMA (1,0,0) for Inner Gamis Hijab products. The supplies provided for Batik C-Geulis products in July 2021 are 37 pcs, Busui C-Geulis are 45 pcs, and Inner Gamis C-Geulis are 49 pcs.